Meiotic chromosome pairing in triploid and tetraploid Saccharomyces cerevisiae - Loidl, J. (University of Vienna, Vienna, Austria.) (Genetics (Austin), 1995)
Meiotic chromosome pairing in isogenic triploid and tetraploid strains of yeast and the consequences of polyploidy on meiotic chromosome segregation are studied. Synaptonemal complex formation at pachytene was found to be different in the triploid and in the tetraploid. In the triploid, triple-synapsis, that is, the connection of three homologues at a given site, is common. It can even extend all the way along the chromosomes. In the tetraploid, homologous chromosomes mostly come in pairs of synapsed bivalents. Multiple synapsis, that is, synapsis of more than two homologues in one and the same region, was virtually absent in the tetraploid. About five quadrivalents per cell occurred due to the switching of pairing partners. From the frequency of pairing partner switches it can be deduced that in most chromosomes synapsis is initiated primarily at one end, occasionally at both ends and rarely at an additional intercalary position. In contrast to a considerably reduced spore viability (approximately 40% ) in the triploid, spore viability is only mildly affected in the tetraploid. The good spore viability is presumably due to the low frequency of quadrivalents and to the highly regular 2:2 segregation of the few quadrivalents that do occur. Occasionally, however, quadrivalents appear to be subject to 3:1 nondisjunction that leads to spore death in the second generation